2018
DOI: 10.1161/circinterventions.117.006074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vascular Closure Devices Versus Manual Compression After Femoral Artery Puncture in Women

Abstract: Background: The value of vascular closure devices (VCD) in women undergoing transfemoral catheterization has not been sufficiently investigated. Methods and Results: This is a sex-specific analysis of 1395 women enrolled in a large-scale, randomized, multicenter trial, in which patients undergoing transfemoral diagnostic coronary angiography were randomly assigned in a 1:1:1 ratio to arteriotomy closure with an intravascular VCD, extravas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…The predictors of bleeding-associated complications such as the female sex, anticoagulant use, a large sheath size, and manual compression, identified in previous studies [12][13][14][15][16][17][18], were not significant in this study. The implication is that the increased risk due to these factors is offset by performing an "optimal puncture" with the ultrasound-guided puncture of the CFA.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The predictors of bleeding-associated complications such as the female sex, anticoagulant use, a large sheath size, and manual compression, identified in previous studies [12][13][14][15][16][17][18], were not significant in this study. The implication is that the increased risk due to these factors is offset by performing an "optimal puncture" with the ultrasound-guided puncture of the CFA.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies have reported that patient predictors of bleeding-associated complications were increasing age and the female sex [12,17]. Applegate RJ revealed that increasing age was associated with bleeding-associated complications (OR = 1.02, 95% CI 1.01-1.03, p<0.001) in 34,556 patients who underwent percutaneous cardiac catheterization via the CFA [24].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, due to a lower bodyweight compared with men, periprocedural heparin dose might have been relatively high. In accordance with Gewalt et al, 12 there was no interaction of VCD treatment effect with sex.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to femoral catheterization, vascular complication rates with vascular closure devices (VCDs) in women are inconsistent across studies. 133,134 The Instrumental Sealing of Arterial Puncture Site -CLOSURE Device versus Manual Compression (ISAR-CLOSURE) trial reported similar rates of vascular access-site complications in women receiving a VCD compared with those receiving manual compression (8.6% vs. 9.8%; p¼0.451), 133 whereas other studies have reported reduced or even higher vascular complications with VCD in women. [135][136][137] As such, the optimal manner of achieving hemostasis at the access site in women undergoing transfemoral cardiac catheterization is not defined.…”
Section: Vascular Access In Womenmentioning
confidence: 99%